Accessibility for People with Disabilities in Public Services at UPTD LIPONSOS Kalijudan Surabaya City Social Service - vancouver, Achmad; Kriswibowo, Arimurti (Universitas Muhammadiyah Ponorogo, 2024)
In fulfilling human rights, there must be no provisions that exclude and align one person with another regardless of the shortcomings and advantages of each person, including no difference in treatment for normal people and people with disabilities. Persons with disabilities have the right to obtain justice for the availability of public services. For mankind, the principle of justice is an important principle that humans crave as the highest ideal of mankind. The existence of 4 aspects that have been explained in the Surabaya City regional regulations, namely Convenience, Usability, Safety and Independence, are expected to be able to improve accessibility for people with disabilities. The research method used is descriptive qualitative method with literature study and observation in the form of interviews. The results showed that in the aspect of convenience, it is quite good even though there are still some things that have not shown maximum results such as the absence of handrail facilities leading to the bathroom and handrails for wheelchair users, then for aspects of usability, convenience and independence have shown very good results.